In-situ lossless soft probe based on metal aerogel composite material and preparation method of in-situ lossless soft probe

Through the combination of metal aerogel with conductive or dielectric polymer and pulsed laser processing, an in-place non-destructive soft probe with a three-dimensional network structure is formed, solving the physical damage of traditional probes for component detection and elasticity of conductive glue-based probes. The problem of insufficient achieves high elasticity and environmental stability, and is suitable for solder joint detection and performance testing in the modern semiconductor industry.

CN119199207APending Publication Date: 2024-12-27HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411160900.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional metal-based probes are prone to physical damage during component detection. The conductive glue-based probes are insufficient elasticity and poor environmental stability, which cannot meet the needs of modern semiconductor industry for miniaturized and high-density component solder joint detection and performance testing. .

Method used

Using in-place non-destructive soft probes based on metal aerogel composites, a three-dimensional network structure is formed by combining metal aerogel with conductive or dielectric polymers, and optionally filled with insulated flexible polymers, and is formed by pulsed laser processing. Array, improve elasticity and stability.

Benefits of technology

It achieves high elasticity, excellent electrical performance and environmental stability, can maintain conductive properties under compressed state, adapt to various shapes and deformations, extend service life, and is suitable for solder joint detection and performance testing in electronic packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119199207A_ABST
    Figure CN119199207A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ lossless soft probe based on a metal aerogel composite material and a preparation method of the in-situ lossless soft probe. The in-situ lossless soft probe comprises a substrate, wherein bonding pads which are distributed in an array are preset on the substrate; a metal aerogel composite material array, wherein the metal aerogel composite material array is arranged on the bonding pad; the metal aerogel composite material comprises metal aerogel, the metal aerogel is of a three-dimensional network structure, and the surface of the metal aerogel is coated with a conductive polymer or a dielectric polymer. The metal aerogel composite material disclosed by the invention has excellent elasticity, electrical properties and structural stability; the conductive polymer or the dielectric polymer is uniformly coated on the nano-scale metal aerogel with a three-dimensional network structure, so that the metal aerogel has excellent compression stability performance while meeting high conductivity, and the metal aerogel becomes an in-situ lossless soft probe with high compression stability performance; the device is widely applied to device welding spot detection and performance testing in electronic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of probe technology, and in particular to an in-situ non-destructive soft probe based on a metal aerogel composite material and a preparation method thereof. Background Art

[0002] With the rapid development of the semiconductor industry, integrated circuits are gradually developing towards miniaturization, high density and high power, which has led to the solder joint detection and performance testing of small components becoming an urgent problem to be solved. Probe detection is a method of solder joint failure detection, which directly contacts the probe with the solder joint to achieve solder joint detection and performance testing of components.

[0003] At present, metal-based and conductive glue-based probes are mainly used for solder joint detection and performance testing of components. However, traditional metal-based probes are prone to physical damage to components and PCB boards during testing, such as surface scratches and defects; while conductive glue-based probes are made of high-filling precious metal-based conductive glue, which has limited elasticity, high requirements for supporting processing and dispensing equipment, and are expensive. They have poor high temperature and environmental stability and are prone to losing elasticity or aging and conductivity degradation under loads such as temperature and humidity. Therefore, in order to ensure the working performance and service life of components and PCB boards, it is of great significance to develop new probes. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an in-situ non-destructive soft probe based on metal aerogel composite materials and a preparation method thereof, aiming to solve the problems that traditional metal-based probes are prone to cause physical damage to components and PCB boards when testing components, and that conductive glue-based probes have insufficient elasticity and poor high temperature and environmental stability.

[0005] Metal aerogel is a porous material with a three-dimensional network structure, which has low density, good elasticity and flexibility, extremely high conductivity, and strong thermal-electro-chemical stability. Because it has a three-dimensional porous network structure, it provides the possibility of compounding with various high molecular polymers. Based on this, the present invention utilizes the special three-dimensional porous network structure of metal aerogel, adopts the skeleton formed by metal aerogel, and the conductive polymer or dielectric polymer coated on the surface of the metal aerogel, so as to obtain a metal aerogel composite material, and can also fill the pores of the metal aerogel with an insulating flexible polymer. The preparation method is to first prepare the metal aerogel, and then mix the metal aerogel with a conductive polymer monomer solution or a dielectric polymer monomer solution to obtain a metal aerogel composite material. The obtained metal aerogel composite material has excellent elasticity, electrical properties and stability, and then fills or does not fill with an insulating flexible polymer. Filling with an insulating flexible polymer can improve toughness and strength.

[0006] Specifically, the technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides an in-situ nondestructive soft probe based on a metal aerogel composite material, comprising:

[0008] A substrate, on which solder pads distributed in an array are preset;

[0009] A metal aerogel composite material array, wherein the metal aerogel composite material array is disposed on the pad;

[0010] Among them, metal aerogel composite materials include:

[0011] A metal aerogel having a three-dimensional network structure.

[0012] A conductive polymer or a dielectric polymer coated on the surface of the metal aerogel.

[0013] Optionally, the in-situ nondestructive soft probe further comprises: an insulating flexible polymer filled in the metal aerogel composite material array.

[0014] Optionally, the conductive polymer is selected from one or more of polypyrrole, polyacetylene, polyphenylene, polyacene, polythiophene, polyaniline and polysulfide;

[0015] The dielectric polymer is selected from one or more of polyimide, biaxially oriented polypropylene, polytetrafluoroethylene, polyethyleneimine, polyphenylene sulfide, and polyphenylene sulfide modified products;

[0016] The insulating flexible polymer is selected from one or more of polydimethylsiloxane, epoxy resin, phenolic resin, polyurethane, polyimide, urea-formaldehyde resin and silicone resin.

[0017] The second aspect of the present invention provides a method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material according to the present invention, which comprises:

[0018] Step A, providing a metal aerogel composite material, wherein the metal aerogel composite material comprises a metal aerogel and a conductive polymer or a dielectric polymer coated on the surface of the metal aerogel;

[0019] Step B, providing a substrate, wherein the substrate is pre-set with solder pads distributed in an array;

[0020] Step C, mounting the metal aerogel composite material on the array-distributed pads, performing array processing on the metal aerogel composite material by pulsed laser, obtaining a metal aerogel composite material array on the pads, and obtaining an in-situ nondestructive soft probe based on the metal aerogel composite material.

[0021] Optionally, after step C is completed, the method further includes:

[0022] Step D: filling the metal aerogel composite material array with an insulating flexible polymer solution, and then curing it to obtain the in-situ non-destructive soft probe based on the metal aerogel composite material.

[0023] Optionally, the step D specifically includes: filling the metal aerogel composite array with an insulating flexible polymer solution by a percolation compounding method, then placing it in a vacuum box for low-pressure degassing, and then placing it on a heating platform for heating and curing to obtain the in-situ non-destructive soft probe based on the metal aerogel composite material.

[0024] Optionally, in step C, the parameters for array processing of the metal aerogel composite material by pulse laser include: laser power of 0.5W to 5W, and laser processing speed of 25mm / min to 300mm / min.

[0025] The third aspect of the present invention provides an in-situ nondestructive soft probe based on a metal aerogel composite material, comprising:

[0026] Insulating flexible polymer films;

[0027] A metal aerogel composite material array embedded in the insulating flexible polymer film;

[0028] Among them, metal aerogel composite materials include:

[0029] A metal aerogel having a three-dimensional network structure.

[0030] A conductive polymer or a dielectric polymer coated on the surface of the metal aerogel.

[0031] Optionally, the conductive polymer is selected from one or more of polypyrrole, polyacetylene, polyphenylene, polyacene, polythiophene, polyaniline and polysulfide;

[0032] The dielectric polymer is selected from one or more of polyimide, biaxially oriented polypropylene, polytetrafluoroethylene, polyethyleneimine, polyphenylene sulfide, and polyphenylene sulfide modified products;

[0033] The insulating flexible polymer is selected from one or more of polydimethylsiloxane, epoxy resin, phenolic resin, polyurethane, polyimide, urea-formaldehyde resin and silicone resin.

[0034] A fourth aspect of the present invention provides a method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material according to the present invention, which comprises the following steps:

[0035] Step A', providing a smooth substrate and a metal aerogel composite material, wherein the metal aerogel composite material comprises a metal aerogel and a conductive polymer or a dielectric polymer coated on the surface of the metal aerogel;

[0036] Step B', forming a sacrificial layer on the smooth substrate;

[0037] Step C', cutting and compressing the metal aerogel composite material into a layered metal aerogel composite material, placing the layered metal aerogel composite material on the surface of the sacrificial layer, and sequentially pressing and curing;

[0038] Step D', performing array processing on the cured metal aerogel composite material by pulse laser to obtain a metal aerogel composite material array located on the sacrificial layer;

[0039] Step E', filling the insulating flexible polymer solution into and between the metal aerogel composite material arrays, and after curing, immersing in a desorption solvent to dissolve the sacrificial layer to obtain an in-situ nondestructive soft probe based on the metal aerogel composite material.

[0040] Beneficial effects: The in-situ nondestructive soft probe based on the metal aerogel composite material of the present invention has at least the following advantages:

[0041] First, the metal aerogel composite material of the present invention has excellent elasticity, electrical properties and environmental stability. The metal aerogel in the metal aerogel composite material has a three-dimensional network structure, which can maintain the three-dimensional network structure without collapse when compressed, twisted and bent, and there will be no conductive network disconnection, and the elasticity is excellent; and the conductive polymer or dielectric polymer can be evenly coated on the three-dimensional network structure of the metal aerogel, while meeting the high conductivity, it also has excellent compression stability. The conductivity of the metal aerogel composite material under compression can reach 10 6 -10 7 S / m, which is far superior to traditional conductive adhesive materials, can be compressed by more than 90%, and can better adapt to various shapes and deformations.

[0042] Second, the metal aerogel composite material of the present invention uses a metal aerogel with an internal porosity of more than 99% as a matrix. The ultra-large porosity can be used to fill insulating flexible polymers. Different insulating flexible polymers can be used to meet application requirements of different flexibility and temperature, and have a wide range of applications. For example, polydimethylsiloxane can be used in scenes below 200°C, with high stability and transparency; silica gel can be used in scenes below 300°C; polyimide can be used in scenes above 300°C.

[0043] Third, the metal aerogel composite material of the present invention has strong environmental stability, self-hydrophobicity, acid and alkali resistance, etc., and can be quickly patterned to form the required probe array for completing device solder joint detection and customized testing of device performance in electronic packaging. Specifically, according to the solder joint distribution map, the metal aerogel composite material can be arrayed by laser processing to form probes of various sizes above 10μm, such as large-area probes for power devices and fixed impedance fine-pitch probes for chips (using dielectric polymer coating), so as to better cope with different application scenarios, and laser array processing can maintain extremely high processing accuracy. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A schematic top view of an in-situ nondestructive soft probe based on a metal aerogel composite material provided in an embodiment of the present invention.

[0045] Figure 2 A schematic flow chart of another method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material provided in an embodiment of the present invention.

[0046] Figure 3 This is a SEM image of the silver nanowire network uniformly coated with polypyrrole in Example 1. DETAILED DESCRIPTION

[0047] The present invention provides an in-situ nondestructive soft probe based on a metal aerogel composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0048] According to one embodiment of the present invention, there is provided an in-situ non-destructive soft probe based on a metal aerogel composite material, such as Figure 1 As shown, including:

[0049] A substrate, wherein the substrate (which may be a rigid PCB board or a flexible PCB board) is provided with pads arranged in an array;

[0050] A metal aerogel composite material array, wherein the metal aerogel composite material array is disposed on the pad;

[0051] Among them, metal aerogel composite materials include:

[0052] A metal aerogel having a three-dimensional network structure.

[0053] A conductive polymer or a dielectric polymer coated on the surface of the metal aerogel.

[0054] In the embodiments of the present invention, the metal aerogel composite material has good elasticity, electrical properties and structural stability. The metal aerogel has an adjustable three-dimensional nano-network structure, and the conductive polymer or dielectric polymer can be evenly coated on the three-dimensional network structure at the nanoscale. While meeting the high conductivity, it also has excellent compression stability, making it an in-situ non-destructive soft probe with high compression stability, which is widely used in device solder joint detection and performance testing in electronic packaging. The preparation method of the metal aerogel composite material is simple and has good repeatability.

[0055] According to one embodiment of the present invention, the material of the metal aerogel is metal nanowires, that is, a metal aerogel having a three-dimensional network structure formed by cross-linking metal nanowires. The solid phase size and pore size of the metal aerogel are both in the nanometer order.

[0056] According to one embodiment of the present invention, the metal nanowires are selected from one or more of silver nanowires, copper nanowires, nickel nanowires, gold nanowires and tin nanowires.

[0057] In a preferred embodiment, the metal nanowires are silver nanowires.

[0058] According to one embodiment of the present invention, the diameter of the metal nanowire is 30nm-1000nm (such as 30nm, 50nm, 60nm, 80nm, 100nm, 300nm, 400nm, 600nm, 900nm, 1000nm, etc.), the gap size between the metal nanowires is 40nm-100μm (such as 40nm, 50nm, 60nm, 80nm, 100nm, 300nm, 400nm, 600nm, 900nm, 1μm, 10μm, 30μm, 50μm, 60μm, 80μm, 100μm, etc.), and the density of the metal nanowire is 1mg / cm 3 -600mg / cm 3 (e.g. 1mg / cm 3 、10mg / cm 3 、50mg / cm 3 、100mg / cm 3 、200mg / cm 3 、300mg / cm 3 , 400mg / cm 3 , 500mg / cm 3 、550mg / cm 3 、600mg / cm 3 As well as specific point values ​​between the above point values, due to space limitations and for the sake of brevity, the present invention will no longer exhaustively list the specific point values ​​included in the range.

[0059] According to one embodiment of the present invention, the conductive polymer is selected from one or more of polypyrrole, polyacetylene, polyphenylene, polyacene, polythiophene, polyaniline and polysulfide. The conductive polymer can be greatly compressed and has excellent conductive properties and resilience.

[0060] In a preferred embodiment, the conductive polymer is polypyrrole, which can be compressed to a greater extent, has better conductivity, and can withstand more than 50,000 times of resilience.

[0061] According to one embodiment of the present invention, the dielectric polymer is selected from one or more of polyimide, biaxially oriented polypropylene, polytetrafluoroethylene, polyethyleneimine, polyphenylene sulfide, and polyphenylene sulfide modified products. When the compression resistance needs to remain unchanged, the dielectric polymer is selected to coat the metal aerogel. The above dielectric polymer can be greatly compressed and has excellent resilience.

[0062] According to one embodiment of the present invention, the ratio of the diameter of the metal nanowire to the thickness of the coated conductive polymer is 20:1-1:20, such as 1:20, 1:10, 1:1, 2:1, 3:1, 4:1, 6:1, 10:1, 15:1, 18:1, 20:1, etc.; or, the ratio of the diameter of the metal nanowire to the thickness of the coated dielectric polymer is 20:1-1:20, such as 1:20, 1:10, 1:1, 2:1, 3:1, 4:1, 6:1, 10:1, 15:1, 18:1, 20:1, etc.

[0063] According to one embodiment of the present invention, the in-situ nondestructive soft probe further includes: an insulating flexible polymer filled in the metal aerogel composite material array.

[0064] The metal aerogel composite material uses a metal aerogel with an internal porosity of more than 99% as the matrix. The ultra-large porosity can be used to fill the insulating flexible polymer. Filling the metal aerogel composite array with insulating flexible polymer is conducive to improving the strength and toughness of the in-situ non-destructive soft probe.

[0065] According to an embodiment of the present invention, the insulating flexible polymer is selected from one or more of polydimethylsiloxane, epoxy resin, phenolic resin, polyurethane, polyimide, urea-formaldehyde resin and silicone resin. In the embodiment of the present invention, different insulating flexible polymers can be used to meet application requirements of different flexibility and temperature.

[0066] In a preferred embodiment, the insulating flexible polymer is polydimethylsiloxane, because the material has better stability and elasticity.

[0067] According to one embodiment of the present invention, 40%-100% (such as 40%, 50%, 60%, 70%, 80%, 90%, 100%, etc.) of the pores of the metal aerogel are filled with the insulating flexible polymer to form a porous or fully filled structure based on a metal nanowire network.

[0068] According to one embodiment of the present invention, a method for preparing an in-situ non-destructive soft probe based on a metal aerogel composite material is provided, which comprises:

[0069] Step A, providing a metal aerogel composite material, wherein the metal aerogel composite material comprises a metal aerogel and a conductive polymer or a dielectric polymer coated on the surface of the metal aerogel;

[0070] Step B, providing a substrate, wherein the substrate is pre-set with solder pads distributed in an array;

[0071] Step C, mounting the metal aerogel composite material on the array-distributed pads, performing array processing on the metal aerogel composite material by pulsed laser, obtaining a metal aerogel composite material array on the pads, and obtaining an in-situ nondestructive soft probe based on the metal aerogel composite material.

[0072] According to one embodiment of the present invention, in step C, the metal aerogel composite material is mounted on the pads distributed in an array using a thin layer of silver paste. The metal aerogel composite material of a desired size and shape is mounted on the pads distributed in an array using a thin layer of silver paste.

[0073] According to one embodiment of the present invention, in step C, the parameters of array processing of the metal aerogel composite material by pulsed laser include: laser power of 0.5W to 5W (such as 2W), laser processing speed of 25mm / min to 300mm / min (such as 100mm / min). Through laser array processing, a metal aerogel composite material array that is conformal and stably connected to the pad array can be obtained.

[0074] According to one embodiment of the present invention, after step C is completed, the method further includes:

[0075] Step D: filling the metal aerogel composite material array with an insulating flexible polymer solution, and then curing it to obtain the in-situ non-destructive soft probe based on the metal aerogel composite material.

[0076] According to one embodiment of the present invention, the step D specifically includes: adding an insulating flexible polymer solution to the metal aerogel composite material array by a percolation compounding method, then placing it in a vacuum box for low-pressure degassing, and then placing it on a heating platform for heating and curing to obtain the in-situ non-destructive soft probe based on the metal aerogel composite material.

[0077] Wherein, the insulating flexible polymer solution comprises an insulating flexible polymer and a curing agent.

[0078] Wherein, the curing agent is selected from one or more of commonly used cross-linking agents, end-capping agents and the like.

[0079] The low-pressure degassing time may be 5-15 min, such as 10 min.

[0080] The temperature of the heating and curing may be 70-90° C., such as 80° C.; and the time of the heating and curing may be 0.5-1 h, such as 0.5 h.

[0081] According to one embodiment of the present invention, there is provided an in-situ nondestructive soft probe based on a metal aerogel composite material, comprising:

[0082] Insulating flexible polymer films;

[0083] A metal aerogel composite material array embedded in the insulating flexible polymer film;

[0084] Among them, metal aerogel composite materials include:

[0085] A metal aerogel having a three-dimensional network structure.

[0086] A conductive polymer or a dielectric polymer coated on the surface of the metal aerogel.

[0087] In the embodiments of the present invention, the metal aerogel composite material has good elasticity, electrical properties and structural stability. The metal aerogel has an adjustable three-dimensional nano-network structure, and the conductive polymer or dielectric polymer can be evenly coated on the three-dimensional network structure at the nanoscale. While meeting the high conductivity, it also has excellent compression stability, making it an in-situ non-destructive soft probe with high compression stability, which is widely used in device solder joint detection and performance testing in electronic packaging.

[0088] In the embodiment of the present invention, the in-situ nondestructive soft probe is an independent device, and the soft probe can be flexibly replaced according to the use requirements, and the strength and toughness of the soft probe are greatly improved after being filled with insulating flexible polymer.

[0089] The specific details about the metal aerogel composite material are mentioned above and will not be repeated here.

[0090] According to one embodiment of the present invention, a method for preparing an in-situ non-destructive soft probe based on a metal aerogel composite material is provided, such as Figure 2 As shown, the following steps are included:

[0091] Step A', providing a smooth substrate 2 and a metal aerogel composite material, wherein the metal aerogel composite material comprises a metal aerogel and a conductive polymer or a dielectric polymer coated on the surface of the metal aerogel;

[0092] Step B', forming a sacrificial layer 1 on the smooth substrate 2;

[0093] Step C', cutting and compressing the metal aerogel composite material into a layered metal aerogel composite material, placing the layered metal aerogel composite material 3 on the surface of the sacrificial layer 1, and sequentially pressing and curing;

[0094] Step D', performing array processing on the cured metal aerogel composite material by pulse laser to obtain a metal aerogel composite material array 4 located on the sacrificial layer;

[0095] Step E', filling the insulating flexible polymer solution 5 into and between the metal aerogel composite material arrays, and after curing, immersing in a desorption solvent to dissolve the sacrificial layer 1 to obtain an in-situ nondestructive soft probe 6 based on the metal aerogel composite material.

[0096] According to an embodiment of the present invention, in the step A', the smooth substrate may be a flat substrate such as a silicon wafer or a glass plate.

[0097] According to an embodiment of the present invention, in the step B', the material of the sacrificial layer may be one of polyvinyl alcohol (PVA) and polymethyl methacrylate (PMMA).

[0098] According to an embodiment of the present invention, in the step B', the thickness of the sacrificial layer may be 10-40 μm.

[0099] According to an embodiment of the present invention, in the step C', the curing temperature is 70-90° C. (eg, 80° C.) and the curing time is 30-60 min (eg, 30 min).

[0100] According to one embodiment of the present invention, in step D', the parameters for array processing of the cured metal aerogel composite material by pulse laser include: laser power of 0.5W to 5W (such as 0.8W), laser processing rate of 25mm / min to 300mm / min (such as 50mm / min).

[0101] According to an embodiment of the present invention, in the step E', the curing temperature is 50-80°C (such as 80°C) and the curing time is 20-40 minutes (such as 30 minutes).

[0102] According to an embodiment of the present invention, in step E', the desorption solvent is one of water and acetone. When the sacrificial layer material is PVA, water is selected as the desorption solvent; when the sacrificial layer material is PMMA, acetone is selected as the desorption solvent.

[0103] The preparation method of the metal aerogel composite material of the present invention is introduced below.

[0104] According to one embodiment of the present invention, a method for preparing a metal aerogel composite material is provided, which comprises the following steps:

[0105] S1. providing metal aerogel;

[0106] S2. Mixing the metal aerogel with a conductive polymer monomer solution or a dielectric polymer monomer solution for a first predetermined time to form a conductive polymer or a dielectric polymer on the surface of the metal aerogel to obtain the metal aerogel composite material.

[0107] In an embodiment of the present invention, when a conductive polymer is formed on the surface of the metal aerogel, the preparation method comprises: preparing the metal aerogel; mixing a diluted low-solubility conductive polymer monomer solution with the metal aerogel, using an oxidant such as silver nitrate to release Ag; + The oxidizability of the metal aerogel and the self-adsorption effect of the reaction products on the metal nanowires such as nanosilver wires during the oxidation reaction form a conductive polymer on the surface of the metal aerogel through in-situ growth. The metal aerogel composite material has good elasticity, electrical properties and structural stability. The preparation method of the metal aerogel composite material is simple, repeatable, mature and reliable, and has low environmental requirements. It is expected to solve the current problems of solder joint detection and performance testing of small components. At the same time, the metal aerogel composite material has obvious application advantages compared with traditional conductive adhesive materials.

[0108] In an embodiment of the present invention, when a dielectric polymer is formed on the surface of the metal aerogel, the preparation method includes: preparing the metal aerogel; mixing a diluted low-solubility dielectric polymer monomer solution with the metal aerogel, and growing the dielectric polymer monomer on the surface of the metal aerogel by in-situ polymerization under heating conditions to form a dielectric polymer, thereby obtaining the metal aerogel composite material. The metal aerogel composite material has good elasticity, electrical properties and structural stability. The preparation method of the metal aerogel composite material is simple, has good repeatability, a mature and reliable process flow, and low environmental requirements, and is expected to solve the current problems of solder joint detection and performance testing of small components. At the same time, the metal aerogel composite material has obvious application advantages compared to traditional conductive adhesive materials.

[0109] In step S1, in one embodiment, the metal aerogel is prepared by the following method: preparing a metal hydrogel skeleton by liquid phase induced reduction method, washing and drying the metal hydrogel skeleton to obtain the metal aerogel. The metal aerogel can be cut into a specified size according to the actual drawing size.

[0110] In one embodiment, the reducing agent used in the liquid phase induced reduction method is ethylene glycol, the reaction temperature is 120° C.-150° C., and the reaction time is 3 h-5 h.

[0111] In one embodiment, the drying method is freeze drying or supercritical drying; preferably supercritical drying.

[0112] In one embodiment, the drying time is 3h-10h.

[0113] The preparation method of metal aerogel is prior art and will not be described in detail here.

[0114] In step S2, in one embodiment, the metal aerogel is mixed with a conductive polymer monomer solution for a first predetermined time to form a conductive polymer on the surface of the metal aerogel. The step of obtaining the metal aerogel composite material specifically includes:

[0115] Providing a conductive polymer monomer solution, wherein the conductive polymer monomer solution comprises a conductive polymer monomer, an oxidant and a solvent;

[0116] The metal aerogel is completely immersed in a conductive polymer monomer solution for a first predetermined time to form a conductive polymer on the surface of the metal aerogel, and then washed and dried to obtain the metal aerogel composite material, wherein the first predetermined time is 1h-48h, such as 1h, 5h, 10h, 13h, 15h, 20h, 25h, 30h, 33h, 35h, 40h, 45h, 48h, etc. As well as specific point values ​​between the above point values, the present invention no longer exhaustively lists the specific point values ​​included in the range due to space limitations and for simplicity.

[0117] In one embodiment, the conductive polymer monomer solution comprises a conductive polymer monomer, an oxidant and a solvent (such as a mixed solution of water and ethanol, etc.). Preferably, the oxidant is silver nitrate. Preferably, the conductive polymer monomer is selected from one or more of pyrrole, acetylene, phenylene, acene, thiophene, aniline and thioether.

[0118] Preferably, in the conductive polymer monomer solution, the concentration of the conductive polymer monomer is 0.1 μM-1M (such as 0.1 μM, 0.5 μM, 1 μM, 2 μM, 3 μM, 10 μM, 20 μM, 50 μM, 80 μM, 100 μM, 500 μM, 800 μM, 1M, etc.), and the concentration of the oxidant is 0.1 μM-1M (such as 0.1 μM, 0.5 μM, 1 μM, 2 μM, 3 μM, 10 μM, 20 μM, 50 μM, 80 μM, 100 μM, 500 μM, 800 μM, 1M, etc.). The use of low concentrations of conductive polymer monomers and oxidants can make the reaction slow and uniform, thereby ensuring that a conductive polymer coating layer with uniform thickness is formed on the surface of the metal aerogel.

[0119] In one embodiment, the step of mixing the metal aerogel with a dielectric polymer monomer solution for a first predetermined time to form a dielectric polymer on the surface of the metal aerogel to obtain the metal aerogel composite material specifically includes:

[0120] providing a dielectric polymer monomer solution, the dielectric polymer monomer solution comprising a dielectric polymer monomer and a solvent;

[0121] The metal aerogel is completely immersed in a dielectric polymer monomer solution, reacted under heating conditions for a first predetermined time to form a dielectric polymer on the surface of the metal aerogel, and then washed and dried to obtain the metal aerogel composite material, wherein the heating temperature is 200-250°C (such as 220°C), and the first predetermined time is 0.1h-4h, such as 0.1h, 0.5h, 1h, 2h, 3h, 4h, etc. As well as specific point values ​​between the above point values, the present invention no longer exhaustively lists the specific point values ​​included in the range due to space limitations and for simplicity.

[0122] In one embodiment, the dielectric polymer monomer solution includes a dielectric polymer monomer and a solvent; preferably, the dielectric polymer monomer is selected from one or more corresponding monomers such as polyimide, biaxially oriented polypropylene, polytetrafluoroethylene, polyethyleneimine, polyphenylene sulfide, and polyphenylene sulfide modifications.

[0123] Preferably, in the dielectric polymer monomer solution, the volume concentration of the dielectric polymer monomer is 0.1-10%, such as 0.1%, 0.5%, 1%, 5%, 10%, etc. As well as specific point values ​​between the above point values, the present invention no longer exhaustively lists the specific point values ​​included in the above range due to space limitations and for the sake of simplicity. The use of low concentrations of dielectric polymer monomers can make the reaction slow and uniform, thereby ensuring that a dielectric polymer coating layer of uniform thickness is formed on the surface of the metal aerogel.

[0124] According to one embodiment of the present invention, there is provided an application of an in-situ non-destructive soft probe based on a metal aerogel composite material in device solder joint detection in electronic packaging.

[0125] According to one embodiment of the present invention, there is provided an application of an in-situ non-destructive soft probe based on a metal aerogel composite material in device performance detection in electronic packaging.

[0126] The present invention will be further described below by means of specific examples.

[0127] Example 1

[0128] A method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material, the specific method comprising:

[0129] (1) preparing a 0.1M AgNO3 precursor aqueous solution, adding a 0.12M citric acid reducing agent, a 0.03M polyvinyl pyrrolidone surfactant and a catalyst in sequence, reacting at 150°C for 6 hours, inducing a liquid phase reduction reaction to prepare a silver nanowire hydrogel, and drying the silver nanowire hydrogel into a silver nanowire aerogel by a supercritical drying method, and cutting and compressing the silver nanowire aerogel by a laser beam and a hydraulic method to obtain a layered silver nanowire aerogel with a thickness of 5 mm;

[0130] (2) compressing a 5 mm thick silver nanowire aerogel into a 2 mm thick silver nanowire aerogel, and then immersing it in a mixed solution containing 2 μM pyrrole, 3 μM silver nitrate, 15 mL water and 15 mL ethanol for 24 h, and drying it for 1 h by supercritical drying to obtain a polypyrrole-coated metal aerogel;

[0131] (3) Using a thin layer of silver glue, the polypyrrole-coated metal aerogel obtained in step (2) is mounted on the target pad array, and the polypyrrole-coated metal aerogel is array-processed by pulsed laser to obtain a polypyrrole-coated metal aerogel array that is conformal and stably connected to the pad array, wherein the laser power is selected to be 2 W and the laser processing speed is selected to be 100 mm / s; then, polydimethylsiloxane and a curing agent are mixed in a volume ratio of 10:1, placed in a vacuum box for low-pressure degassing for 2 minutes, and allowed to stand for 15 minutes to obtain a polydimethylsiloxane solution, and then 21g of polydimethylsiloxane is compounded with the polypyrrole-coated metal aerogel array structure by a percolation composite method, and placed in a vacuum box for low-pressure degassing for 10 minutes, and then placed on a heating platform for heating and curing, the curing temperature is 80°C, and the curing time is 0.5h, so that an in-situ non-destructive soft probe based on a metal aerogel composite material can be obtained. Figure 1 .

[0132] After testing, the electrical conductivity of the polypyrrole-coated metal aerogel obtained in step (2) of this embodiment can reach 20000 S / m. The SEM image of the polypyrrole-coated metal aerogel is shown in FIG. Figure 2 Due to the low concentration of pyrrole and oxidant, the reaction is slow and uniform, and a polypyrrole coating layer with uniform thickness can be formed on the surface of the metal aerogel. The polypyrrole-coated metal aerogel has a low modulus and stable compression performance, and the interior can be well filled with polydimethylsiloxane.

[0133] The conductivity of the in-situ nondestructive soft probe based on the metal aerogel composite material obtained in step (3) can reach 10,000 to 30,000 S / m, and the diameter of a single probe can reach 10 microns. The compression amount of the soft probe can reach 80%, and the number of compressions can exceed 100,000 times, which can be applied to the performance testing of devices and chips of various sizes.

[0134] Example 2

[0135] A method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material, such as Figure 3 As shown ( Figure 3 In the figure, 1 is a PVA sacrificial layer, 2 is a silicon wafer, 3 is a layered polyimide-coated metal aerogel, 4 is a polyimide-coated metal aerogel array, 5 is silica gel, and 6 is an in-situ nondestructive soft probe based on a metal aerogel composite material), and the specific method includes:

[0136] (1) preparing a 0.1M AgNO3 precursor aqueous solution, adding a 0.12M citric acid reducing agent, a 0.03M polyvinyl pyrrolidone surfactant and a catalyst in sequence, reacting at 150°C for 6 hours, inducing a liquid phase reduction reaction to prepare a silver nanowire hydrogel, and drying the silver nanowire hydrogel into a silver nanowire aerogel by a supercritical drying method, and cutting and compressing the silver nanowire aerogel by a laser beam and a hydraulic method to obtain a layered 10 mm thick silver nanowire aerogel;

[0137] (2) compressing a 10 mm thick silver nanowire aerogel into a 1 mm thick silver nanowire aerogel, and then immersing it in 30 mL of a 2 vol.% polyimide monomer solution, reacting it at 220° C. for 2 h, and drying it by supercritical drying for 2 h to obtain a polyimide-coated metal aerogel;

[0138] (3) Spin-coating a 30 μm thick PVA sacrificial layer on a silicon wafer, placing the polyimide-coated metal aerogel obtained in step (2) on the surface of the sacrificial layer, gently pressing it into the sacrificial layer, and heating at 80° C. for 30 min to complete curing;

[0139] (4) processing the polyimide-coated metal aerogel array by pulse laser, wherein the laser power is 0.8 W and the laser processing speed is 50 mm / s, to obtain a polyimide-coated metal aerogel array located on the sacrificial layer;

[0140] (5) Silica gel and curing agent were mixed in a volume ratio of 10:1, placed in a vacuum box for low-pressure degassing for 2 minutes, and allowed to stand for 15 minutes to obtain a silica gel solution. The obtained solution was filled in and between the polyimide-coated metal aerogel arrays, with the liquid level lower than the top surface of the polyimide-coated metal aerogel array. After sufficient standing and degassing treatment, the solution was heated at 80°C for 30 minutes to complete the curing of the polymer. The obtained structure was then immersed in desorption solvent water to dissolve the sacrificial layer, thereby obtaining an in-situ non-destructive soft probe based on the metal aerogel composite material.

[0141] Compared with Example 1, the soft probe of this embodiment is an independent device and can be replaced according to the needs of use. After being filled with silicone, the strength and toughness of the soft probe are greatly improved. It can withstand pressure above 150PSI and rebound spontaneously, but the compressibility is reduced to only about 50%.

[0142] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. An in-situ nondestructive soft probe based on metal aerogel composite material, characterized in that: include: A substrate, on which solder pads distributed in an array are preset; A metal aerogel composite material array, wherein the metal aerogel composite material array is disposed on the pad; Among them, metal aerogel composite materials include: A metal aerogel having a three-dimensional network structure. A conductive polymer or a dielectric polymer coated on the surface of the metal aerogel.

2. The in-situ nondestructive soft probe based on metal aerogel composite material according to claim 1, characterized in that: The in-situ nondestructive soft probe further comprises: an insulating flexible polymer filled in the metal aerogel composite material array.

3. The in-situ nondestructive soft probe based on metal aerogel composite material according to claim 2, characterized in that: The conductive polymer is selected from one or more of polypyrrole, polyacetylene, polyphenylene, polyacene, polythiophene, polyaniline and polysulfide; The dielectric polymer is selected from one or more of polyimide, biaxially oriented polypropylene, polytetrafluoroethylene, polyethyleneimine, polyphenylene sulfide, and polyphenylene sulfide modified products; The insulating flexible polymer is selected from one or more of polydimethylsiloxane, epoxy resin, phenolic resin, polyurethane, polyimide, urea-formaldehyde resin and silicone resin.

4. A method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material according to claim 1, characterized in that: include: Step A, providing a metal aerogel composite material, wherein the metal aerogel composite material comprises a metal aerogel and a conductive polymer or a dielectric polymer coated on the surface of the metal aerogel; Step B, providing a substrate, wherein the substrate is pre-set with solder pads distributed in an array; Step C, mounting the metal aerogel composite material on the array-distributed pads, performing array processing on the metal aerogel composite material by pulsed laser, obtaining a metal aerogel composite material array on the pads, and obtaining an in-situ nondestructive soft probe based on the metal aerogel composite material.

5. The method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material according to claim 4, characterized in that: After step C is completed, the method further includes: Step D: filling the metal aerogel composite material array with an insulating flexible polymer solution, and then curing it to obtain the in-situ non-destructive soft probe based on the metal aerogel composite material.

6. The method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material according to claim 5, characterized in that: The step D specifically includes: filling the metal aerogel composite material array with an insulating flexible polymer solution by a percolation compounding method, then placing it in a vacuum box for low-pressure degassing, and then placing it on a heating platform for heating and curing to obtain the in-situ non-destructive soft probe based on the metal aerogel composite material.

7. The method for preparing an in-situ nondestructive soft probe based on aerogel composite material according to claim 4, characterized in that: In the step C, the parameters for array processing of the metal aerogel composite material by pulse laser include: laser power of 0.5W to 5W, and laser processing speed of 25mm / min to 300mm / min.

8. An in-situ non-destructive soft probe based on metal aerogel composite material, characterized in that: include: Insulating flexible polymer films; A metal aerogel composite material array embedded in the insulating flexible polymer film; Among them, metal aerogel composite materials include: A metal aerogel having a three-dimensional network structure. A conductive polymer or a dielectric polymer coated on the surface of the metal aerogel.

9. The in-situ nondestructive soft probe based on metal aerogel composite material according to claim 8, characterized in that: The conductive polymer is selected from one or more of polypyrrole, polyacetylene, polyphenylene, polyacene, polythiophene, polyaniline and polysulfide; The dielectric polymer is selected from one or more of polyimide, biaxially oriented polypropylene, polytetrafluoroethylene, polyethyleneimine, polyphenylene sulfide, and polyphenylene sulfide modified products; The insulating flexible polymer is selected from one or more of polydimethylsiloxane, epoxy resin, phenolic resin, polyurethane, polyimide, urea-formaldehyde resin and silicone resin.

10. A method for preparing an in-situ nondestructive soft probe based on a metal aerogel composite material according to any one of claims 8 to 9, characterized in that: The following steps are involved: Step A', providing a smooth substrate and a metal aerogel composite material, wherein the metal aerogel composite material comprises a metal aerogel and a conductive polymer or a dielectric polymer coated on the surface of the metal aerogel; Step B', forming a sacrificial layer on the smooth substrate; Step C', cutting and compressing the metal aerogel composite material into a layered metal aerogel composite material, placing the layered metal aerogel composite material on the surface of the sacrificial layer, and sequentially pressing and curing; Step D', performing array processing on the cured metal aerogel composite material by pulse laser to obtain a metal aerogel composite material array located on the sacrificial layer; Step E', filling the insulating flexible polymer solution into and between the metal aerogel composite material arrays, and after curing, immersing in a desorption solvent to dissolve the sacrificial layer to obtain an in-situ nondestructive soft probe based on the metal aerogel composite material.